2023
DOI: 10.3390/bioengineering10020133
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Body Composition and Inter-Examiner Errors for Assessing Lumbar Multifidus Muscle Size, Shape and Quality Metrics with Ultrasound Imaging

Abstract: Ultrasound imaging (US) is widely used in several healthcare disciplines (including physiotherapy) for assessing multiple muscle metrics such as muscle morphology and quality. Since measuring instruments are required to demonstrate their reliability, accuracy, sensitivity, and specificity prior to their use in clinical and research settings, identifying factors affecting their diagnostic accuracy is essential. Since previous studies analyzed the impact of sociodemographic but not body composition characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Up to the authors’ knowledge, this is the first study investigating the association between demographic and body composition features with SWE errors. However, this is not the first study analyzing the test–retest reliability of SWE for quantifying the AS stiffness [ 32 ] or aiming to analyze the association between US errors with anthropometric, demographic, and body composition characteristics [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to the authors’ knowledge, this is the first study investigating the association between demographic and body composition features with SWE errors. However, this is not the first study analyzing the test–retest reliability of SWE for quantifying the AS stiffness [ 32 ] or aiming to analyze the association between US errors with anthropometric, demographic, and body composition characteristics [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Varol et al found age to be one of the most important contributors to B-mode US measurement errors for assessing cross-sectional area, circularity, aspect ratio, roundness, and mean echo intensity (defined as the average brightness intensity of pixels, measured on a 256 grayscale, over a given area) characteristics of the lumbar multifidus [ 33 ] and the mean echo-intensity of the cervical multifidus [ 34 ]. Additionally, water volume was reported to be another important contributor to B-mode measurement errors, as it was correlated with lumbar multifidus cross-sectional area errors [ 33 ] and cervical multifidus cross sectional areas, perimeters, and roundness measurement errors [ 34 ]. In parallel to our SWE results, BMI did not influence any B-mode metric measurement error in these studies [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound imaging (US) is a fast, cost-effective, and portable tool used for diagnostics (i.e., assessing the muscle size, shape, quality, and function in other neck muscles [ 17 , 18 , 19 ]) and therapeutic (i.e., needle guidance for invasive procedures and as a biofeedback tool for facilitating the learning and execution of motor control exercises [ 20 , 21 ]) purposes. In addition, advances in US methods for assessing tissues’ elasticity (i.e., shear-wave elastography, SWE) allow clinicians and researchers to acquire quantitative and objective stiffness data with absolute values (in contrast with strain technology, which is limited to relative information) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, US is portable, safe (as no ionizing radiation is used for acquiring the images), fast, accessible and provides real-time information, allowing the examination of immediate changes [ 8 ]. Due to these advantages and the range of imaging methods based on US (e.g., B-mode, M-mode, Doppler US, strain elastography, shear-wave elastography and panoramic US, among others [ 9 ]), it is a tool that is widely used in health sciences for the educational (i.e., teaching anatomy and pathologies [ 10 ]), research (i.e., to obtain objective measurements of muscle function, size, shape and composition [ 11 ]) and clinical settings (e.g., as a supportive tool for guiding needle interventions, visual feedback for motor control exercises or monitoring changes after interventions [ 12 ]). However, important limitations should be acknowledged.…”
Section: Introductionmentioning
confidence: 99%